Applications of Topological Photonics in Integrated Photonic Devices. Issue 18 (1st August 2017) - Wu, You; Li, Chong; Hu, Xiaoyong; Ao, Yutian; Zhao, Yifan; Gong, Qihuang
Abstract : Topological photonics is an emerging field of research, which is inspired by the discovery of topological insulators. The introduction of topology endows traditional photonic systems with brand new properties, including unidirectional propagating edge states and robustness against impurities or defect without backscattering. With the further development of theoretical research on topological photonics, many new photonic devices have been proposed and experimentally demonstrated, showing its broad prospects in constructing high‐performance integrated photonic chips. Topology, as a new research perspective in photonics, is expected to bring about remarkable changes to the field of integrated photonic devices and optical interconnection. This review summarizes the fundamental realization principles of topology in photonic systems, comparison of topology in photonics and electronics, applications of topological photonics in integrated photonic devices and related optical effects. Finally, a brief outlook on the challenges and future development direction in the pursuit of the application of topological photonics in integrated photonic devices is provided. Abstract : As an emerging field of research, topological photonics has been developing quickly in recent years and has shown enormous potential for applications in integrated photonic devices. This review summarizes the fundamental realization principles, comparison of topology in photonics and electronics, applications of topological photonics in integrated photonic devices, related optical effects, and the research status and challenges in this field.